Minimally Invasive Mitral Valve Repair with Intercostal Cryoablation: A Case Report - Humpfle, Luisa; Böning, Andreas; Niemann, Bernd; Justus Liebig University Giessen (My University, 2024)
Background: Minimally invasive lateral thoracotomies may cause severe postoperative pain and discomfort. We describe an intraoperative intercostal cryo-neuronal pain block as one possibility for postoperative pain relief. Case description: A 63-year-old male patient underwent minimally invasive mitral valve repair. To reduce postoperative pain, an intercostal cryo-neuronal ablation was performed. The consecutive course was pain-free. Conclusion: Intraoperative cryo-neuronal nerve block may be a standard procedure during minimally invasive cardiac surgery.
Keywords: ddc:610